2020
DOI: 10.1073/pnas.2003873117
|View full text |Cite
|
Sign up to set email alerts
|

Global tree-ring analysis reveals rapid decrease in tropical tree longevity with temperature

Abstract: Forests are the largest terrestrial biomass pool, with over half of this biomass stored in the highly productive tropical lowland forests. The future evolution of forest biomass depends critically on the response of tree longevity and growth rates to future climate. We present an analysis of the variation in tree longevity and growth rate using tree-ring data of 3,343 populations and 438 tree species and assess how climate controls growth and tree longevity across world biomes. Tropical trees grow, on average,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 72 publications
3
33
1
4
Order By: Relevance
“…Survival rates within the tropics decreases with increasing aridity, e.g. (Locosselli et al 2020), yet we find no evidence of an effect of mean annual precipitation on DD, possibly because DD is also defined by growth rates and stature in our analysis, which may show little correlation with precipitation. DC is mostly unrelated to temperature and precipitation, with the exception that the relative abundance of large-statured species decreases with increasing MAT.…”
Section: There Is Moderate Evidence For a Relationship Between Climat...contrasting
confidence: 51%
“…Survival rates within the tropics decreases with increasing aridity, e.g. (Locosselli et al 2020), yet we find no evidence of an effect of mean annual precipitation on DD, possibly because DD is also defined by growth rates and stature in our analysis, which may show little correlation with precipitation. DC is mostly unrelated to temperature and precipitation, with the exception that the relative abundance of large-statured species decreases with increasing MAT.…”
Section: There Is Moderate Evidence For a Relationship Between Climat...contrasting
confidence: 51%
“…The positive feedbacks can also be evidenced by the conclusion that the biomass resilience of Neotropical secondary forests strongly depends on water availability 55 . In the context of global warming, high temperature would result in increases in tree mortality in the tropics due to the higher evaporation and increasing aridity 56 . Our results indicated that boreal forest regions were more sensitive to precipitation rather than temperature, which is consistent with previous findings that water availability is becoming increasingly important for boreal forest productivity 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Anomalously dry years are associated with tropical seas surface temperature anomalies [34][35][36]; high temperatures and low humidity provide favorable conditions for the rapid spread of fires [37,38]. These extreme-drought events have the potential to destabilize large areas by reducing rainfall and thereby increasing the risk of forest death [39], which could, in turn, lead to the further intensification of regional droughts as a result of vegetation loss [40]. A warmer and drier climate can lead to the mortality of plant species adapted to wetter climates [4], as well as a decrease in water recycling in the central part of the Amazon [41,42].…”
Section: Introductionmentioning
confidence: 99%